IMPROVING LEARNER AUTONOMY VIA ONLINE TASKS FOR B1 LEARNERS - Faxriyeva, Dilorom (MMIT Proceedings, 2023)
The current article investigates the urgency, actuality and assessing the effect of online learning activities on the academic achievements of students who took part in a blended learning program, with a particular emphasis on skill-based courses. Typically, a student's learning outcomes are evaluated based on their attained scores, knowledge, or skills throughout the course. In blended learning programs, the learning outcomes can be evaluated based on various criteria. The study focuses on interactive activities, such as teacher-student interactions, that were used to evaluate the learning outcomes of the participants.